ETNOMATEMATIKA PEMBUATAN KERAJINAN TANGAN ANYAMAN BAMBU MASYARAKAT OSING DI DESA GINTANGAN BANYUWANGI SEBAGAI BAHAN AJAR GEOMETRI - Fajar, Fahmi Alan; Sunardi, S; Yudianto, Erfan (Kadikma, 2018)
Ethnomatematics is the application of mathematics in cultural life. The purpose of this study was to describe ethnomatematics of making woven bamboo handicrafts in the village of Gintangan Banyuwangi. The things obtained in this study were changed in the form of geometric teaching materials, namely the Test Problem Package with the topic of Ethnomatematics. This type of research is qualitative with an ethnographic approach. Data collection methods used are observation and interviews. The subjects of the study were 2 people, namely a foreman making woven bamboo crafts, kukusan, ereg, tenong, and nyiru and a maker of bamboo woven kukusan, ereg, tenong, and nyiru. Ethnomatematics emerged when the woven craftsmen carried out activities to measure, calculate and design. When the process of measuring the thickness of the bamboo sharpener comes the measurement concept using meters (m). During the process of calculating the drying time of bamboo and the amount of bamboo sharpener a comparative concept of value appears. During the design process, the concept of quadrilateral and number sequences emerged. The results of the study are geometry teaching materials in the form of a test test package. The question test package is intended for class VIII middle school students. This Question Test Package consists of 4 C5 and 1 C6 questions Keywords: Ethnomatematics, Bamboo Woven Crafts, Geometry